Stercoral Perforation of the Colon during Pregnancy: A Case Report and Review of the Literature - Costales, Anthony B.; Agarwal, Amit K.; Chauhan, Suneet P.; Refuerzo, Jerrie S.; Taub, Ethan A. (American Journal of Perinatology Reports, 2015)
Stercoral perforation of the colon, though rare, is associated with high mortality. Review of the literature identified only three prior cases reported during pregnancy. We report a case on a multiparous female presenting at 31 weeks of gestation with acute abdominal pain. Computed tomography suggested a sigmoid colon perforation. An urgent exploratory laparotomy was performed where feculent peritonitis and a stercoral perforation of the sigmoid colon was confirmed. A cesarean delivery and sigmoid colectomy with descending end colostomy was performed. While the newborn had an uncomplicated course, the mother developed an intra-abdominal abscess requiring operative management.
Keywords: colonic perforation; pregnancy; stercoral perforation